Studies of high-membered two-dimensional Ruddlesden–Popper Cs7Pb6I19 perovskite nanosheets via kinetically controlled reactions. Issue 9 (18th July 2022) - Chen, Yi-Chia; Wu, Kuan-Chang; Chen, Hsin-An; Chu, Wen-Hui; Gowdru, Swathi M.; Lin, Jou-Chun; Lin, Bi-Hsuan; Tang, Mau-Tsu; Chang, Chia-Che; Lai, Ying-Huang; Kuo, Tsung-Rong; Wen, Cheng-Yen; et al.
Abstract : A new path to the discovery of 2D perovskite structures with metastable phases was demonstrated by using a recrystallization method and the assistance of sulfur-derived organic molecules. Their kinetic formation mechanisms were also investigated. Abstract : Two-dimensional (2D) all-inorganic Ruddlesden–Popper (RP) perovskite Cs7 Pb6 I19 nanosheets (NSs) were successfully developed for the first time by employing a structural recrystallization process with additional passivation of small organic sulfide molecules. The structure of Cs7 Pb6 I19 NSs is confirmed by powder X-ray diffraction measurements, atomically-resolved STEM measurements and atomic force microscopy (AFM) studies. Cs7 Pb6 I19 NSs with a specific n value of 6 exhibits unique absorption and emission spectra with intense excitons at 560 nm due to quantum confinement effects in 2D perovskite slabs. The formation mechanisms of 2D Cs7 Pb6 I19 NSs and 3D γ-CsPbI3 phases were investigated by in situ photoluminescence (PL) spectroscopy and the activation energies of their formation reactions were calculated to be 151 kJ mol −1 and 95.3 kJ mol −1, respectively. The phase stability of 2D Cs7 Pb6 I19 NSs can be maintained at temperatures below 14 °C for more than 4 weeks. The overall results indicate that 2D Cs7 Pb6 I19 NSs demonstrate unique optical properties and structural stability compared with other 3D perovskite materials. We have opened a new path to the future discovery of 2D perovskite structures with metastable phases by using this recrystallization method and the assistance of sulfur-derived organic molecules.